Metode ARIMA untuk Memodelkan Volume Produksi Kelapa Sawit pada PT. SOCFINDO di Kabupaten Aceh Tamiang - Wiwin Apriani; Rahmi Hayati (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2021)
This study aims to create a mathematical model that can be used to predict the amount of oil palm that will be produced at PT. Socfindo in Aceh Tamiang Regency in the coming period. The data used is data on the amount of oil palm that is ready to be produced every month in 2012-2015. The method used is the ARIMA method. The selection of this method is based on the data used, namely time series data. Before carrying out further testing, first, ensure that the data used meets the stationary state. From the test results, it is found that the data used fulfills the stationary state, then it is found that the MA (1) model can be used to predict the time series data. Furthermore, we obtain a model that can be used to predict the volume of oil palm production at PT. Socfindo is: Z_t = a_t-0.4096a_ (t-1) +521.57 With a_t N (0; 29192.72)